Immunoprevalence and magnitude of HLA-DP4 versus HLA-DR-restricted spontaneous CD4+ Th1 responses against telomerase in cancer patients. (3rd May 2016) - Laheurte, Caroline; Galaine, Jeanne; Beziaud, Laurent; Dosset, Magalie; Kerzerho, Jerome; Jacquemard, Claire; Gaugler, Béatrice; Ferrand, Christophe; Dormoy, Anne; Aubin, François; Jacoulet, Pascale; Westeel, Virginie; et al.
ABSTRACT: Cumulative evidence supports that CD4 + Th1 cells play a key role in antitumor immunity. We previously reported the presence of spontaneous HLA-DR-restricted CD4 + Th1 responses against telomerase reverse transcriptase (TERT) in various cancers by using promiscuous HLA-DR epitopes. Here, we described novel highly immunogenic HLA-DP4-binding epitopes from TERT named TERT541–555, TERT573–587, TERT613–627 and TERT911–925 and addressed the question about the immunoprevalence and magnitude of the naturally occurring antitumor CD4 + T cell responses restricted by HLA-DP4 or HLA-DR, the two most common HLA class II. Direct comparative study of spontaneous anti-TERT CD4 + T cell responses in a cohort of 87 lung cancer patients showed that HLA-DP4 and HLA-DR sustained specific Th1 responses in 10.1% and 25.2% of cancer patients respectively ( p = 0.01). The magnitude of the HLA-DR-restricted responses was two to three times significantly higher than HLA-DP one ( p = 0.005). Similar results were found in other cancers such as melanoma, breast cancer, renal cell carcinoma and colon cancer. Thus, our results describe for the first time in a large cohort of cancer patients a high immunoprevalence of HLA-DR-restricted spontaneous anti-TERT Th1 immunity compared to HLA-DP restriction. These results provide a new tool for comprehensive monitoring of antitumor CD4 + Th1 response in various cancers.